Estudio técnico para el diagnóstico de problemáticas en bienestar animal en las intervenciones asistidas con caninos - Sánchez Cuadros, Leidy Paola (Universidad Antonio Nariño, 2022)
Since their domestication more than 30,000 years ago, dogs have played an important role in the evolution of humanity (Glenk, 2017). The strength of the human-animal connection allowed canines to rapidly adopt multiple roles within societies human: as a hunter, shepherd, messenger, protector, with the purpose of satisfying the ends and human interests. However, animals also have interests: avoiding pain, fear, distress, or physical harm, and pursuing their own needs, wants, and goals (Serpell et al. 2010).